STABILITY ANALYSIS OF FOUR TYPES OF POLE AND LINER - St. Aisyah Farhum (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2010)
This study was purposed to compare the stability of four types of pole and liner casco (round bottom, round flat bottom, round sharp bottom and u-v bottom),. The stability value was analyzed by calculating the stability on the curve with the heeling angle of 0-90°. The stability results of each casco type were then compared with the criteria of minimum standard value derived from IMO (International Maritime Organization). Results showed that the four casco types had greater stability values than IMO standard values. This study found that the stability value of the round –sharp bottom casco was better than the others.Keywords: Stability of fishing boat, Pole and liner, casco